3D atom probe study of gas adsorption and reaction on alloy catalyst surfaces II: Results on Pt and Pt-Rh - Bagot, P; Cerezo, A; Smith, G (2007)
The 3-dimensional atom probe (3DAP) is a unique instrument providing chemical analysis at the atomic scale for a wide range of materials. A dedicated 3DAP has been built specifically for analysing reactions at metal surfaces, called the catalytic atom probe (CAP). This paper presents an overview of results from the CAP on structural and chemical transformations to surface layers of Pt and Pt-17.4 at.%Rh catalysts following exposure to a number of gases typically emitted by vehicle engine exhausts, normally for 15 min at pressures of 10 mbar. Following exposure to the oxidising gases NO on Pt, and NO, O2 or N2O on Pt-Rh, both surfaces appear disrupted, while for Pt-Rh, Rh enrichment of the surface atomic layer is noted over the entire specimen apex for exposure temperatures up to 523 K. However, for oxidising exposures at 573-773 K relatively clean, Rh-depleted surfaces are observed on {0 0 1}, {0 1 1} and {0 1 2} crystallographic regions of Pt-Rh. It is suggested that this result is due to surface diffusion of oxide species over the specimen apex, towards the {1 1 1}-orientated areas where the oxides appear to be stabilised. In contrast, CO exposure appears to have little effect on the either the surface structure or composition of the Pt-Rh alloy. Finally, combinations of two gases (NO + CO, O2 + NO) were also dosed onto Pt-Rh alloys in the same exposure. These revealed that while NO and CO can co-adsorb without interference, CO prevents the build up of oxide layers and reduces the extent of Rh segregation seen under NO exposure alone. On exposing Pt-Rh to NO after an oxygen exposure, heavily oxidised surfaces, Rh segregation and no intact NO molecules were seen, confirming the ability of oxidised Pt-Rh to dissociate nitric oxide. © 2007 Elsevier B.V. All rights reserved.